1979
DOI: 10.1111/j.1365-3083.1979.tb03279.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage/T‐Lymphocyte Interaction in the Immune Response to PPD in Humans

Abstract: The proliferative response of sensitized human T cells to low concentrations of purified protein derivative of tuberculin (PPD) in vitro has previously been shown to depend on the presence of autologous or HLA-D-compatible macrophages (M phi). In this paper we present evidence that the M phi/T cell interaction requires viable M phi and does not involve a soluble factor. T cells from neonates do not respond to PPD in our system, while M phi from neonates are able to present PPD to T cells from HLA-D matched sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…4). Of the two tested antigens, PPD represents a well-characterized positive control antigen that is meant to define our experimental T-cell system (35). Cartilage-derived collagen type II, on the other hand, is currently studied with great interest as a possible autoimmunogen of importance in rheumatoid arthritis (37,38).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…4). Of the two tested antigens, PPD represents a well-characterized positive control antigen that is meant to define our experimental T-cell system (35). Cartilage-derived collagen type II, on the other hand, is currently studied with great interest as a possible autoimmunogen of importance in rheumatoid arthritis (37,38).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…It is known that monocytes in fluence the afferent and efferent Limb of the immune response: the antigen presentation depends on T cell activation [3,5,6,15]. We, therefore, suggest that due to the lack of anti gen-responding lymphocytes under ALG treatment, the less ALG-sensitive monocytes increase in the graft during rejection epi sodes.…”
Section: Discussionmentioning
confidence: 91%
“…We, therefore, suggest that due to the lack of anti gen-responding lymphocytes under ALG treatment, the less ALG-sensitive monocytes increase in the graft during rejection epi sodes. In addition it has been reported [3,16] that high concentrations of monocytes result in diminished immune response. The opti mal activation of T lymphocytes seems to be reached at day 7.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoproliferative response in vitro are also regulated by M a [14, 161 and may be initiated by antigen-fed M a [3,[16][17][18][19][20]. Although most investigators suggest that either MQ [3, 4, 17, 211 or their soluble products [22, 231 are essential for this response, other investigators have shown that T lymphocyte proliferation may also be induced independently of MQ [20, 22, 241. In human systems, it is as yet unclear which of the MQ functions is an essential part of the lymphoproliferative response against soluble antigen.…”
Section: Oncology Sharett Institute Of Hadassah School Of Medicine mentioning
confidence: 99%